Aseptic abscess syndrome as first manifestation of Crohn's disease - a case report - Ambrozová, Martina; Hrunka, Matěj; Ježová, Marta; Urík, Milan; Jabandžiev, Petr (BMC pediatrics, 2025)
BACKGROUND: There exist multiple extraintestinal manifestations of inflammatory bowel disease. The most common are arthritis, aphthous stomatitis, or uveitis. Aseptic abscess syndrome is not usually included among these extraintestinal manifestations. In our case report, we present a rare case of aseptic abscess syndrome as the first manifestation of inflammatory bowel disease. CASE PRESENTATION: We present the case of a 10-year-old girl whose only initial medical issue was recurrent submandibular lymphadenitis unresponsive to standard antibiotic therapy. A broad differential diagnosis was initiated to exclude an infectious etiology. Eventually, it was necessary to proceed with extirpation of the suspected lymph node. Histological examination showed suppurative granulomatous inflammation, so it was further examined for noninfectious cause. Blood tests revealed positivity of ASCA antibodies (Anti-Saccharomyces cerevisiae) in both IgA and IgG classes. Despite absence of typical gastrointestinal symptoms, bowel ultrasound was performed, followed by magnetic resonance enterography. Both showed inflammatory changes in the terminal ileum. Subsequent endoscopy of the gastrointestinal tract and histological examination of biopsy specimens confirmed a diagnosis of Crohn's disease with terminal ileum and rectum involvement. A standard treatment based on current guidelines led to remission without recurrence of lymphadenitis. CONCLUSIONS: In cases of lymphadenitis that does not respond to standard antibiotic treatment, diagnosis of aseptic abscess syndrome should be considered as a potential etiology and, subsequently, inflammatory bowel disease should be investigated, given that this syndrome is associated with inflammatory bowel disease in as many as 70% of cases. To our knowledge, this is the first published case report describing aseptic abscess syndrome affecting cervical lymph nodes as an extraintestinal manifestation of pediatric Crohn's disease.
Keywords: Extraintestinal manifestation; diferenciální diagnóza; Female; dítě; Abscess; ženské pohlaví; lidé; Crohn’s disease; Diagnosis, Differential; lymfadenitida; Crohn Disease; Aseptic abscess syndrome; absces; Syndrome; Child; Crohnova nemoc; Pediatrics; Inflammatory bowel disease; Lymphadenitis; syndrom; Humans